ESP students’ views of ESL grammar learning - Sadiq Abdulwahed Ahmed Ismail, (Penerbit UKM, 2010)
Grammar has always been viewed as playing an essential role in the success or failure of formal communication. This research will show that grammar education should be ‘descriptive’ rather than ‘prescriptive’ in order to offer students a set of choices to make them effective speakers and writers. The main objective of this study was twofold. First, it focused on students’ views about a new grammar model that includes four stages: confrontation, clarification, confirmation and consolidation (CCCC) and students’ perceptions regarding grammar learning in general. Second, it investigated the recurrent patterns of interaction during the process of learning grammar within the framework of the model. The subjects of this study were forty female students from three ESP for education classes in the UAE University. Three research instruments (a questionnaire, classroom observation notes and semi-structured interviews) were employed to establish data triangulation and to attain validity. The results from the collective data demonstrated that students had positive views about the use of the CCCC grammar model. Another crucial result highlighted the students’ beliefs about the positive influence of explicit grammar teaching on learning the conventions of sentences and utterances. Finally, the study concluded with recommendations to direct future research.